An approach to the biogeography of polypore fungi (Agaricomycotina, Basidiomycota) in southern South America - Rajchenberg, Mario (2022)
The polyporoid fungi from the Patagonian Andes forests of Argentina and Chile were analyzed from a biogeographic point of view through the optics of phylogenetic studies. A total of 72 species are accepted, including 4 that are still unpublished. Species were distributed as either Cosmopolitan (14 spp.), Antitropical (7 spp.), Pantropical + Austral-antarctic (3 spp.), Neotropical (4 spp.), South-temperate (= endemic, 28 spp.), Austral-antarctic (14 spp.) or Circum-austral (2 spp.) in distribution. They were recorded in the Valdivian province (71 spp.), but also in the Magellanic province (22 spp.) and the Maule province (21 spp.). Three species were also distributed northward in Chile and other 8 species were also found in Juan Fernández province. Almost 35% of the species are brown wood-rotting taxa, representing a relatively high percentage in the polypore funga of Patagonia as compared with other world regions; they are mostly associated with Nothofagaceae, not conifers as in the North Hemisphere. Nothophellinus proved to be the single endemic genus, Neophellinus is shown to be a sub-Amazonian genus, and Arambarria an austral genus with representatives in southern South America (south of the Tropic of Capricorn) and the Cape floristic region. For each species, a detailed account of the phylogeny is presented according to the literature, along with insights into its geographical distribution and relationships with other taxa in the genus where it is accepted. Austral lineages are highlighted at genus level (Gloeoporellus, Macrohyporia, Neolentiporus, Ryvardenia; incl. 5 species) and species level (another 12 taxa). Ongoing and completed speciation processes are pointed out. The following new combinations are proposed: Cyanosporus venatus, Neophellinus livescens and Postia exigua.